Breast Tumor Diagnosis Using Diode Laser in Near Infrared Region - Munqith S. Dawood (Al-Khwarizmi College of Engineering – University of Baghdad, 2009)
In the last years, new non-invasively laser methods were used to detect breast tumors for pre- and postmenopausal females. The methods based on using laser radiation are safer than the other daily used methods for breast tumor detection like X-ray mammography, CT-scanner, and nuclear medicine.